Efficacy of laparoscopic splenectomy in thalassemia patients - Koshour, Ahmed; Mohamed, Moharam Abdelsamie; A. Elbalshy, Mohammed; Nassar, Mohammed Nazeeh Shaker (International Surgery Journal, 2019)
Background: Haematological disorders in which splenectomy is indicated, the laparoscopic splenectomy became the standard management, except in β thalassemia in which laparoscopic splenectomy still not established yet. Methods: Thirty patients with thalassemia between November 2017 and April 2019 were operated by anterior approach laparoscopic splenectomy with early ligation of splenic artery then the splenic vein ligated. In initial 12 cases the specimen was extracted via the lower flank port after extending the trocar incision to 10 cm, while through a 7-8 cm Pfannenstiel incision in 17 cases and one case converted to open. Results: The procedure was completed in 29 patients while one patient converted to open. The mean age of patients was 15.2±3.8 years. The mean operating time was 104±23.5 minutes (90-120 minutes). The mean intra-operative blood loss was 179±37.2 ml (130-250 ml). No major intra-operative complications occurred. Only one patient required intraoperative blood transfusion. The mean postoperative hospital stay was 2.7 days (2-4 days). Conclusions: Laparoscopic splenectomy is feasible and safe procedure in β thalassemia patients even with huge splenomegaly. The specimen extraction via a Pfannenstiel incision saves more time, carries low morbidity and offer better cosmetic results.